A High Effective Acid System to Stimulate Sandstone Reservoirs. (19th July 2022) - Li, Bin
Abstract : Mud acid is regularly applied to recover or increase permeability of sandstone reservoir. However, due to its rapid reacting rate and heterogeneous displacement, the stimulation effect of conventional mud acid is relatively limited in sandstone formations. For mud acid, it is important to choose proper chemical additives to retard reaction rate and make it distributed homogenereously in formation. To overcome these shortcomings of mud acid, a new proprietary mud acid system has been developed for sandstone formations stimulation. The new system is composed of 2.0% multichemical solutions (MCS) +6.5%HCl+1.5% HF, and the combined solution contains nonionic surfactant, clay stabilizer, and dispersant which were specifically formulated. Core flooding experiments were conducted with the high effective mud acid; meanwhile, XRD and SEM analysis were performed before/after the core flooding tests. Retarded tests were also conducted for the new mud acid reacting with sandstone samples. Treatments with ten pores volume of the new high effective mud acid system were found to increase permeability of sandstone core approximately three times of its initial permeability. From the results of SEM and XRD analysis, most of clays were dissolved, and permeability was increased after core flooding by this new mud acid solution. On the basis of acidizing theory, the reaction retarded mechanism was explained about the new composite mud acid. Other properties of the new composite mud acid were also discussed. In comparison of conventional mud acid, the new composite mud acid can retard acidizing reaction rate and distribute evenly in formation; therefore, it can extend acidizing penetration and stimulate sandstone formation thoroughly. The new composite mud acid is more compatible and desirable than conventional mud acid, and it will be applied extensively for sandstone matrix stimulation.